Preparation of multi-layered (dense-porous) lightweight magnesium-aluminum spinel refractory. Issue 9 (1st May 2021) - Hossain, Sk S.; Roy, P.K.
Abstract: The dense (working) and porous (insulation) refractories are generally used for the lining of any kind of furnaces or kilns. The present investigation provides a new designed spinel (MgAl2 O4 ) light weight refractory, which retains both working and insulation parts in a single specimen. The multi-layered refractories are fabricated by varying the amount of pore-forming agent (rice powder) and sintering aids (waste rice husk ash (RHA)) in the different layers. A porosity gradient is developed by the incorporation of intermediate layers in between the insulation and working layer. At 1550 °C with 3 h soaking sample retains good compressive strength (92.43 MPa), low apparent porosity (8.72%), good cement clinker corrosion resistance in the working layer along with reasonable strength (31.72 MPa), and low thermal conductivity (0.146 W/m·k) in the insulation layer. These promising results may encourage the refractory industries in developing the light weight multi-layered refractory for cement kiln. Highlights: A refractory contains a combination of dense and porous layers for cement kilns. Utilize of multi-layered refractory for cutting down the total mass of kilns. A porosity gradient is developed through the slight changing of the composition. Rice husk ash is used as sintering aid and rice powder as pore-forming agent.